Analysis of Glutamate Exit in Escherichia coli - Halpern, Yeheskel S. (1975)
Escherichia coli B exhibits carrier-mediated first-order exit of glutamate with a half-time of less than 4 min, similar to that observed in K-12 strains. Glutamate exit in both B and K-12 strains is inhibited by arsenite. Practically all of the radioactivity lost during exit by K-12 cells has been accounted for as glutamate in the cell filtrate.